Arketipe Dan Pencarian Makna Diri Dalam Antologi Puisi Hidup Tetap Berjalan Dan Kita Telah Lupa Alasannya Karya Ibe S. Palogai: Kajian Psikologi Sastra Carl Gustav Jung - Larasati, Risky Tri; Aulia Hasanah; Ceria Wulandari; Nur Jibril; Elmustian, Elmustian (CV. ULIL ALBAB CORP, 2026)
This study aims to reveal the psychological dimensions and symbolic values in the poetry anthology Hidup Tetap Berjalan dan Kita Telah Lupa Alasannya by Ibe S. Palogai through the analytical psychology framework of Carl Gustav Jung. Poetry is understood not merely as a product of the poet’s imagination, but also as an expression shaped by social conditions and layers of personal unconsciousness that generate collective symbols. Employing a descriptive qualitative method and intensive reading techniques, this research analyzes 40 poems in the anthology and categorizes them into Jung’s four archetypes: persona, shadow, anima, and self. The findings indicate that the shadow archetype is the most dominant, reflected in strong social criticism, existential anxiety, and inner tension toward modern realities. The persona archetype appears through distorted identity symbols and representations of social masks. The anima archetype is expressed in emotional closeness, dreams, and memories that signal a need for inner healing. Meanwhile, the self archetype emerges in the poet’s deep reflections on meaning, connectedness, and the pursuit of wholeness. Overall, the anthology can be interpreted as a psychological journey toward individuation—the process of understanding, integrating, and discovering the true self. This research offers a novel contribution to literary psychology studies as the first analysis to map all Jungian archetypes within this anthology.